Callaphididae (Aphidoidea) new for Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence in ltaly of Callaphididae Callipterinella tuberculata (von Heyden) and Calaphis flava Mordvilko found on Betula alba; Takecallis taiwanus (Takahashi) found on Phyllostachis mitis and Neophyllaphis podocarpi Takahashi on Podocarpus sp. is pointed out .
Keywords: Callaphididae; Callipterinella tuberculata; Calaphis flava; Takecallis taiwanus; Neophyllaphis podocarpi